Optimal Income Taxation with a Risky Asset: The Triple Income Tax - Dirk Schindler (University of Konstanz, Center of Finance and Econometrics (CoFE), 2003)
We show in a two-period world with endogenous savings and two assets, one of them exhibiting a stochastic return that an interest adjusted income tax is optimal. This tax leaves a safe component of interest income tax free and taxes the excess return with a special tax rate. There is no trade off between risk allocation and efficiency in intertemporal consumption. Both goals are reached. As the resulting tax system divides income into three parts, the tax can also be called a triple income tax. This distinction and a special tax rate on the excess return is necessary in order to have an optimal risk shifting effect.
urn:nbn:de:bsz:352-opus-11670
Keywords: H21; 330; Optimal Taxation; Uncertainty; Consumption Tax; Triple Income Tax; Optimale Besteuerung; Einkommensteuerpolitik; Ausgabensteuer; Risiko; Theorie